Hai Crunch / Ahmad Fawwaz Mirza Rosli - Rosli, Ahmad Fawwaz Mirza (2021)
First and foremost, I would like to express my gratitude to all my friends for their assistance in resolving my ENT300 issues. Next, I would want to express my gratitude to Mrs. Hazelen for her assistance in completing my duties. Then, as part of the project, I had to sell Hai Crunch products. This product has been warmly appreciated by friends and customers, alhamdulillah. I sell things since they help to relieve tension and allow me to eat while completing school or watching movies while also adding to my pocket money. Finally, I chose a product and sold this Hai Crunch through group advertising tactics, and I was pleasantly surprised to discover that it had met my aim of RM 200.00.